STUDI PENANGAN PASCAPANEN KOPI ROBUSTA DI KABUPATEN ALOR - Lalel, Herianus JD; Cakswindryandani, Ni Luh Putu Ravi; Abidin, Zainal (JURNAL AGRISA, 2023)
Robusta coffee is interesting to many people because of its flavor and it has a good price. Postharvest handling of the commodity plays an important role in its quality. A research has been conducted at Alor Regency to study how the postharvest handling applied to the robusta coffee planted in this area. The research was done through the survey method using purposive sampling. The farmer who has robusta coffee plants ≥ 1 ha will be selected, followed by descriptive observation. There is only one farmer who stays at Mainang village that meets the criteria. Postharvest handling of robusta coffee in Mainang village includes harvesting, sun drying, and removing the husk. Harvesting occurs from June to August. In the average of harvested beans, green beans are counted for 7.22%, 11.75% of orange beans, 62.79% of red beans, and 18.24% of blackish-red beans. Sun drying is undergone for 7 to 12 hours. Removing the husk of the beans uses wood mortar followed by shaking. All these processes resulted in 85.28% of clean whole beans, 8.99% of half-broken beans, and 5.72 of full-broken beans. Even though there is a high percentage of whole beans, the result still does not meet SNI standard for coffee beans. Therefore, the postharvest handling for robusta coffee beans in Alor needs to be improved.